2015
DOI: 10.1007/s12603-015-0515-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term mortality in oldest old patients (90+) hospitalized to medical wards via the emergency department: The safes cohort

Abstract: Risk of malnutrition and presence of delirium are risk factors for mortality at 36 months in subjects aged 90 years and over hospitalized through the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Tools predicting short-term falls and mortality post-discharge remain limited and are most often tailored to a specific group of patients based on their disease characteristics (6)(7)(8)(9)(10). Risk factors known to contribute to falls and mortality in hospitalized older patients include poor functional status, poor cognition, illness severity, comorbidities, and polypharmacy (11)(12)(13).…”
mentioning
confidence: 99%
“…Tools predicting short-term falls and mortality post-discharge remain limited and are most often tailored to a specific group of patients based on their disease characteristics (6)(7)(8)(9)(10). Risk factors known to contribute to falls and mortality in hospitalized older patients include poor functional status, poor cognition, illness severity, comorbidities, and polypharmacy (11)(12)(13).…”
mentioning
confidence: 99%
“…Mortality was reported as an outcome in respect of dementia in 16 studies. 12,42,55,56,77,90,97,[105][106][107][108][109][110][111][112][113] Nine studies reported in-hospital mortality. 42,55,77,90,97,105,106,110,111 Seven studies reported post-discharge mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…42,55,77,90,97,105,106,110,111 Seven studies reported post-discharge mortality. 56,105,[107][108][109]112,113 One study reported a statistical difference in in-hospital mortality rates between patients with dementia and delirium, with a higher mortality rate among delirious patients. 97 Four studies found that in-hospital mortality was independently predicted by dementia.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations